The gendered stereotype of the 'good manager': Sex role expectations towards male and female managers - Markus Gmür (Management Revue, 2006)
In the past 30 years, U.S. and international studies have shown that societal expectations of the 'good manager' are closely related to the male stereotype. However, it is not clear, whether this stereotype is the same for men andwomen alike in managerial positions. The results of a German study with 625 students and 376 professionals participating between 1997 and 2005 are presentedin the short note below. The main findings of the study are: 1. Female managers are expected to conform more closely to male stereotypes than are male managers. 2. Higher expectations are set from women and respondents with practical experience than from men and those who are inexperienced. 3. The most recent trend shows that male stereotypes increasingly dominate over female stereotypes. We conclude by emphasizing the importance of highly structured and controlled procedures in order to prevent sex-related discrimination in organizational selection and performance appraisal.
Keywords: 650; manager; selection; sex roles; gender studies; Germany; Führungskräfte; Geschlecht; Weibliche Führungskräfte; Deutschland; Geschlechterforschung